(untitled) (Revista Venezolana de Salud Pública, 2016)
Working conditions, housing and housing including all basic services, schooling, education, free time, citizen security, food and civil liberties, together constitute the conditions for people to enjoy a minimum level of Health. Likewise, equitable access to health care must be the primary objective of any health policy, so studying these elements has been a public health concern as a discipline for many years.